IMPLEMENTATION OF ISLAMIC EDUCATIONAL VALUES IN FORMING STUDENTS' DISCIPLINED CHARACTER - Fathul Amin; Muhaiminah Darajat (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This study aims to describe the implementation of Islamic educational values in shaping students’ disciplinary character at Madrasah Tsanawiyah. The research focuses on the internalization process of aqidah, akhlaq, and ibadah values in developing students’ disciplined behavior, as well as the disciplinary guidance strategies applied by teachers and the institution. This study employs a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that Islamic educational values play an important role in shaping students’ disciplinary character through Islamic Religious Education learning, habituation of religious activities, and teacher role modeling. Disciplinary guidance strategies are carried out through persuasive and humanistic approaches, such as providing rewards, positive reinforcement, rule reminders, personal counseling, and implementation of educational consequences. This approach aligns with Bandura’s social learning theory on behavioral modeling and Skinner’s reinforcement theory emphasizing the importance of positive reinforcement. The implementation of Islamic educational values is proven effective in developing students’ discipline in terms of punctuality, adherence to school regulations, academic responsibility, and consistency in performing worship.